A novel approach to evaluate the benefits of price-based demand response in the unit commitment problem. Issue 1 (February 2021) - Wang, Huiji; Yue, Hao; Zheng, Yanan
Abstract: Price-based demand response (DR) has been widely accepted as playing an important role in the reliable and economic operation of the power system. There are different ways to quantify the electricity consumption experience (i.e., comfort) of customers, which can be divided into positive and negative benefits, that is to say, there is no unified method to evaluate the positive or negative benefits of DR. Based on the self-elasticity and cross-elasticity of price elasticity of demand (PED), this study first addresses a novel approach to evaluate the positive and negative benefits of price-based DR with the consideration of customers' electricity consumption experience. Then, a unit commitment (UC) model considering priced-based DR is built to analyse the influence of priced-based DR on the power system operation, which is linearized into a mixed integer linear programming problem. Finally, the propose method and model are verified the effectiveness through analysing the influence of self-elasticity and cross-elasticity on the power system operation in the IEEE RTS79 system.